Peace education from the grassroots - Servais, Mallory (In Factis Pax: Journal of Peace Education and Social Justice, 2016)
Peace education from the grassroots, edited by Ian M. Harris. A volume in the series: Peace Education, editors Laura Finley & Robin Cooper, Information Age Publishing, 2013, 322pp., US 45.99 (paperback), US 85.99 (hardcover), ISBN 978-1-62396-349-1. Editors note: This review is one in a series co-published by the Global Campaign for Peace Education and In Factis Pax: Journal of Peace Education and Social Justice toward promoting peace education scholarship. These reviews are of Information Age Publishing’s Peace Education series. Established in 2006 by Founding Editors Ian Harris and Edward Brantmeier, IAP’s peace education series offers diverse perspectives on peace education theory, research, curriculum development and practice. It is the only series focused on peace education offered by any major publisher. Click here to learn more about this important series.